Differences in lower-limb alignment and muscle strength between the sexes during distance-specific single-leg hop tasks. - YOSHIMOTO, MASUMI (Journal of Physical Therapy Science, 2026)
[Purpose] This study examined the differences in lower-limb alignment and muscle strength between sexes during distance-specific single-leg hop (SLH) landings. SLH tasks are widely used in rehabilitation and return-to-sport decision-making; however, standardized progression criteria for hop distance are lacking. [Participants and Methods] A total of 59 healthy university participants performed SLH landings at distances set to 30, 50, and 80% of their height. The lower-limb alignment variables and isometric muscle strength were measured. Lower-limb kinematic variables were obtained using three-dimensional motion analysis, and isometric strength of the hip and knee muscles was measured using a handheld dynamometer. [Results] Females demonstrated greater hip flexion angles, lower hip adductor and abductor strength, and lower knee flexor and extensor strength compared to males. No differences were observed between the sexes in terms of vertical ground reaction force, knee valgus angle, or knee valgus moment. Females exhibited a hip-dominant landing strategy and lower strength in specific muscle groups. [Conclusion] The findings of this study highlight the importance of incorporating both movement instruction and strength training during rehabilitation for female athletes. These findings might establish clearer criteria for distance progression during SLH-based rehabilitation programs.